Internal surface pipe roughness classification using high frequency acoustic evaluation - Amar Reza, Mohammad Firdaus (2010)
This project was carried out using the method of acoustic emission analysis to distinguish the internal surface roughness of the pipe. Internal roughness of the pipe is referred to the level of corrosion occurring, where normally it is difficult to be monitored online. Acoustic Emission (AE) technique can be used as an alternative solution to the corrosion monitoring in pipes, especially for complex pipelines and difficult to achieve by other monitoring devices. The objective of this project is to study the AE signals emitted from internal surface pipe and to classify the internal surface pipe roughness using Bangi Number, AB. This study used the hydraulic bench to provide fluid flow at four different pressures in pipes with different internal surface roughness (rough and smooth). The main source of acoustic emission was from activity in the control valve, coupled with high pressure water flow friction in the inner surface of the pipe. The signal from these sources was detected by using the AED-2000V instrument and assisted by the Acoustic Emission Detector (AED) software. The time domain parameter; root mean square, RMS amplitude was processed and compared at different pressures for each type of internal pipe roughness at ten different locations. Based on the RMS values, Bangi Number was derived and can be used for discriminating level of internal surface pipe roughness. Internal surface pipe can still be considered as smooth if AB value is above than 1.0. Meanwhile if AB value is below than 1.0, the inner surface pipe is in rough condition. As conclusion, the acoustic emission technique offers great opportunity for new approaches in monitoring the pipe and it can be used to classify the internal surface pipe roughness.